Recent advances in ZnO based photocatalysts for industrial dye degradation - Andriambahiny Ranto Ny Aina; Harry Patel; Subhajit Aich; Biplab Roy; Niladri Shekhar Samanta; Biswadeep Pal (Discover Applied Sciences)
Abstract Various wastewater treatment techniques are being introduced to minimize the degradation of pollutants. The photocatalytic process is a promising technique for its best possible use of solar energy and being eco-friendly to the environment. Photocatalytic techniques with chemical approaches, nanotechnology, and semi-conductors are considered as sustainable and cost-effective methods. ZnO, a wide-bandgap semiconductor, has garnered considerable interest owing to its elevated photocatalytic efficacy, affordability, low toxicity, and ecological compatibility. However, its actual implementation has been constrained by issues including strong electron–hole coupling and restricted visible light absorption. Recent advancements in ZnO-based photocatalysts aim to overcome these limits by many tactics, such as metal/non-metal doping, heterojunction creation, surface alteration, and nanotechnologies. This review focused on ZnO-based photocatalyst used in dye degradation. Advancements in photocatalytic process as well as hybrid technique are discussed for better efficiency and stability. Various factors like catalyst dosage, pH, temperature, and dye concentration on the degradation process affecting the photocatalytic processes are discussed. Furthermore, the process is easy, non-toxic, and can be associated with a zero waste discharge policy for industrial applications. Challenges are summarized in terms of scalability, health, and safety in addition to fulfilling the growing need for uncontaminated water for multipurpose use. Despite the sustainable processes for mitigation of wastewater, India continues to experience contamination due to its complex behavior.